Clinical Features and Influencing Factors for the Prognosis of Patients With Sudden Deafness - Lin, Wei; Xiong, Gaoyun; Yan, Kailei; Yu, Wumin; Xie, Xiaoxing; Xiang, Ze; Wu, Jian; Ge, Yanping; Wang, Ying (Frontiers in Neurology, 2022)
Backgrounds: Studies on risk factors influencing the prognosis of sudden deafness patients are not complete. Methods: From March 2018 to March 2021, 500 patients with sudden deafness were enrolled from the Tongde Hospital in Zhejiang Province. We collected clinical information from hospital medical records, including certain demographic characteristics, information related to sudden deafness, and laboratory parameters data. The univariate and multivariate analysis were applied to determine independent risk factors for the prognosis of sudden deafness patients. Additionally, we also employed orthogonal partial least squares discriminant analysis (OPLS-DA) to analyse the data of all sudden deafness patients. Results: The baseline clinical characteristics of these included patients were revealed. Based on the prognosis of enrolled patients, the included patients were divided into the overall effective and ineffective groups. Between these two groups, the univariate and multivariate analysis were performed. It was found that age, type of hearing curve at the initial diagnosis, acute phase and sudden deafness site were all independently associated with prognosis in patients with sudden deafness (all P < 0.05). Through the OPLS-DA, sudden deafness site was considered to be an indicator with the highest predictive power. Conclusions: Age, type of hearing curve at the initial diagnosis, acute phase and sudden deafness site were all found to be independently correlated with the prognosis of sudden deafness patients. These factors should be emphasized in sudden deafness patients.